2022
DOI: 10.1017/s0030605322001223
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of the Critically Endangered Primula esquirolii, a karst cave species with an extremely small population endemic to China

Abstract: The rare plant Primula esquirolii, a karst cave species in the family Primulaceae, endemic to Guizhou, China, and with a presumed extremely small population, had not previously been observed since 1910. It is categorized as Endangered on the China Species Red List. In surveys during 2018–2022, we were unable to locate the species in its type location in Pingba county, but we discovered a previously unrecorded population of 44 mature individuals, 37 of which were long homostylous and seven of which were heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…while P. esquirolii and P. pingbaensis occur in the karst areas of Guizhou (usually lower than 1500 m a.s.l.). Field surveys on P. esquirolii showed that it is a species with extremely small populations and was evaluated as‘Critically Endangered’ ( Wu et al 2022 ), like our new finding of P. pingbaensis .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…while P. esquirolii and P. pingbaensis occur in the karst areas of Guizhou (usually lower than 1500 m a.s.l.). Field surveys on P. esquirolii showed that it is a species with extremely small populations and was evaluated as‘Critically Endangered’ ( Wu et al 2022 ), like our new finding of P. pingbaensis .…”
Section: Discussionmentioning
confidence: 60%
“…Species with homostylous morphs are usually accompanied by a compatibility system that makes intramorph (and thus self-) crosses more successful ( Richards 2003 ). The selfing homostylous lineages often have a high genetic load, which makes them sensitive to environmental changes and renders population expansion over short periods difficult ( Wu et al 2022 ). Our observation on Primula species distribution indicated that homostylous species usually have fewer populations or smaller population sizes than closely related heterostylous species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation